A distant shore : a novel - Kingsbury, Karen (Atria Books, 2021)
"She was a child caught in a riptide in the Caribbean Sea. He was a teenager from the East Coast on vacation with his family. He dove in to save her, and that single terrifying moment changed both their lives forever. Ten years later Jack Ryder is a daring secret agent with the FBI and Eliza Lawrence still lives on that pristine island. She's an untainted princess in a kingdom of darkness and evil, on the brink of a forced marriage with a dangerous neighboring drug lord, a marriage arranged by her father. This time when Jack and Eliza meet, there's a connection neither of them can explain. Both their lives are on the line, and once again, the stakes are deadly high. Can they join forces in a complicated and dangerous mission, pretending to have a breathtaking love without really falling? Sometimes miracles happen not once, but twice along a distant shore."--Publisher description.